2015
DOI: 10.1177/1933719114529373
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases 2 and 9 and E-Cadherin Expression in the Endometrium During the Implantation Window of Infertile Women Before In Vitro Fertilization Treatment

Abstract: Objective: To evaluate the expression of endometrial matrix metalloproteinases (MMPs) 2 and 9 and E-cadherin in periimplantation phase of infertile women who have undergone in vitro fertilization (IVF) cycles. Methods: This prospective study included 51 patients who underwent endometrial biopsy during the receptive phase in a menstrual cycle prior to IVF treatment. The samples were evaluated by tissue microarray for immunohistochemical study. Results: The expression of MMP-2, MMP-9, and E-cadherin in the endom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Through the categorized analysis of the 27 articles that composed the final sample, we found that all were published between 2003 and 2019. Of these, 4 were cross-sectional studies ( Pasqualotto et al ., 2003 ; Esteves & Glina, 2005 ; Cota et al ., 2012 ; Souza et al ., 2017 ), 12 were cohort studies ( Pinheiro et al ., 2003 ; Borges et al ., 2003 ; Glina et al ., 2005 ; Pasqualotto et al ., 2005 ; Romão et al ., 2010 ; Semião-Francisco et al ., 2010 ; Cota et al ., 2012 ; Borges et al ., 2013 ; Coelho Neto et al ., 2015 ; Maia-Filho et al ., 2015 ; Scheffer et al ., 2017 ; Bercaire et al ., 2018 ); 6 were case-control studies ( Setti et al ., 2011 ; Pasqualotto et al ., 2012 ; Cavagna et al ., 2012 ; Picinato et al ., 2014 ; Donabela et al ., 2015 ; Costa et al ., 2016 ); 3 were case reports ( Valle et al ., 2012 ; Taitson et al ., 2012 ; Borges et al ., 2016 ) and 2 were randomized controlled trials ( Geber & Sampaio, 2013 ; Nastri et al ., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the categorized analysis of the 27 articles that composed the final sample, we found that all were published between 2003 and 2019. Of these, 4 were cross-sectional studies ( Pasqualotto et al ., 2003 ; Esteves & Glina, 2005 ; Cota et al ., 2012 ; Souza et al ., 2017 ), 12 were cohort studies ( Pinheiro et al ., 2003 ; Borges et al ., 2003 ; Glina et al ., 2005 ; Pasqualotto et al ., 2005 ; Romão et al ., 2010 ; Semião-Francisco et al ., 2010 ; Cota et al ., 2012 ; Borges et al ., 2013 ; Coelho Neto et al ., 2015 ; Maia-Filho et al ., 2015 ; Scheffer et al ., 2017 ; Bercaire et al ., 2018 ); 6 were case-control studies ( Setti et al ., 2011 ; Pasqualotto et al ., 2012 ; Cavagna et al ., 2012 ; Picinato et al ., 2014 ; Donabela et al ., 2015 ; Costa et al ., 2016 ); 3 were case reports ( Valle et al ., 2012 ; Taitson et al ., 2012 ; Borges et al ., 2016 ) and 2 were randomized controlled trials ( Geber & Sampaio, 2013 ; Nastri et al ., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 15.21% of the articles included in this review, endometriosis is cited as the main condition causing female infertility ( Cota et al ., 2012 ; Nastri et al ., 2013 ; Maia-Filho et al ., 2015 ; Picinato et al ., 2014 ; Donabela et al ., 2015 ; Coelho Neto et al ., 2015 ; 2016 ); and in 13.04% azoospermia is the male infertility condition ( Pasqualotto et al ., 2003 ; Glina et al ., 2005 ; Esteves & Glina, 2005 ; Pasqualotto et al ., 2005 ; Semião-Francisco et al ., 2010 ; Taitson et al ., 2012 ). Figure 2 shows the other infertility conditions presented by the patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mid‐secretory endometria of patients with unexplained infertility and recurrent miscarriages, one study reported higher levels of MMP2 and decreased levels of TIMP3 mRNA, but another found that MMP2 and TIMP3 expressions were significantly decreased simultaneously . However, other studies reported that MMP2, MMP9 and TIMP1 expressions in endometrial samples revealed no significant differences between idiopathic infertility, unexplained recurrent miscarriage and control group, and were not associated with IVF pregnancy outcome . This may be related to different sources of the endometrium sample.…”
Section: Discussionmentioning
confidence: 96%
“…MMPs play a critical role in the invasion of trophoblast cells. Among MMPs, MMP2 and 9 seem to be essential in the regulation of invasion and the behaviours of trophoblasts [62][63][64]. During the implantation, trophoblast cells release large amounts of MMP2 and 9 [65].…”
Section: Discussionmentioning
confidence: 99%